The EMT transcription factor ZEB1 governs a fitness-promoting but vulnerable DNA replication stress response. - Schuhwerk, Harald; Kleemann, Julia; Gupta, Pooja; van Roey, Ruthger; Armstark, Isabell; Kreileder, Martina; Feldker, Nora; Ramesh, Vignesh; Hajjaj, Yussuf; Fuchs, Kathrin; Mahapatro, Mousumi; Hribersek, Mojca; et al. (Cell Reports, 2022)
The DNA damage response (DDR) and epithelial-to-mesenchymal transition (EMT) are two crucial cellular programs in cancer biology. While the DDR orchestrates cell-cycle progression, DNA repair, and cell death, EMT promotes invasiveness, cellular plasticity, and intratumor heterogeneity. Therapeutic targeting of EMT transcription factors, such as ZEB1, remains challenging, but tumor-promoting DDR alterations elicit specific vulnerabilities. Using multi-omics, inhibitors, and high-content microscopy, we discover a chemoresistant ZEB1-high-expressing sub-population (ZEB1hi) with co-rewired cell-cycle progression and proficient DDR across tumor entities. ZEB1 stimulates accelerated S-phase entry via CDK6, inflicting endogenous DNA replication stress. However, DDR buildups involving constitutive MRE11-dependent fork resection allow homeostatic cycling and enrichment of ZEB1hi cells during transforming growth factor β (TGF-β)-induced EMT and chemotherapy. Thus, ZEB1 promotes G1/S transition to launch a progressive DDR benefitting stress tolerance, which concurrently manifests a targetable vulnerability in chemoresistant ZEB1hi cells. Our study thus highlights the translationally relevant intercept of the DDR and EMT.
EVALuna2:512403

Zeb1 mediates EMT/plasticity-associated ferroptosis sensitivity in cancer cells by regulating lipogenic enzyme expression and phospholipid composition - Schwab, Annemarie; Rao, Zhigang; Zhang, Jie; Gollowitzer, André; Siebenkäs, Katharina; Bindel, Nino; D’Avanzo, Elisabetta; van Roey, Ruthger; Hajjaj, Yussuf; Özel, Ece; Armstark, Isabell; Bereuter, Leonhard; et al. (Nature Cell Biology, 2024)
Therapy resistance and metastasis, the most fatal steps in cancer, are often triggered by a (partial) activation of the epithelial–mesenchymal transition (EMT) programme. A mesenchymal phenotype predisposes to ferroptosis, a cell death pathway exerted by an iron and oxygen-radical-mediated peroxidation of phospholipids containing polyunsaturated fatty acids. We here show that various forms of EMT activation, including TGFβ stimulation and acquired therapy resistance, increase ferroptosis susceptibility in cancer cells, which depends on the EMT transcription factor Zeb1. We demonstrate that Zeb1 increases the ratio of phospholipids containing pro-ferroptotic polyunsaturated fatty acids over cyto-protective monounsaturated fatty acids by modulating the differential expression of the underlying crucial enzymes stearoyl-Co-A desaturase 1 (SCD), fatty acid synthase (FASN), fatty acid desaturase 2 (FADS2), elongation of very long-chain fatty acid 5 (ELOVL5) and long-chain acyl-CoA synthetase 4 (ACSL4). Pharmacological inhibition of selected lipogenic enzymes (SCD and FADS2) allows the manipulation of ferroptosis sensitivity preferentially in high-Zeb1-expressing cancer cells. Our data are of potential translational relevance and suggest a combination of ferroptosis activators and SCD inhibitors for the treatment of aggressive cancers expressing high Zeb1.
CRIS-Team Scopus Importer:2024-08-02